2013
DOI: 10.1074/jbc.m112.442442
|View full text |Cite
|
Sign up to set email alerts
|

Mild Electrical Stimulation at 0.1-ms Pulse Width Induces p53 Protein Phosphorylation and G2 Arrest in Human Epithelial Cells

Abstract: Background: A controlled approach as opposed to conventional toxic drugs to activate p53 is applicable for tumors and metabolic and inflammatory diseases. Results: A 0.1-ms pulse width mild electrical stimulation (MES) activated p53 function in epithelial cell lines. Conclusion: MES induced p53 phosphorylation via p38 MAPK signaling and G 2 cell cycle arrest without cell death. Significance: MES works as a non-cytotoxic and controllable p53 activator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 63 publications
2
15
0
Order By: Relevance
“…Endogenous electrical field (EF) is known to play an important role in development and is thus an attractive cue to induce stem cell differentiation (Mooney et al ., ; Thrivikraman et al ., ). Electrical stimulation (ES) was shown to increase DNA synthesis (Bourguignon and Bourguignon, ), activate p53 (Fukuda et al ., ), increase TGF β receptor expression (Falanga et al ., ) and upregulate fibroblast growth factor secretion (Rouabhia et al ., ). Cells also responded to exogenous ES via intracellular signalling pathways, such as phosphatidylinositol‐3‐OH kinase (PI3K)–Akt, MAPK–ERKs, integrin and Rho (Fukata et al ., ; Li et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous electrical field (EF) is known to play an important role in development and is thus an attractive cue to induce stem cell differentiation (Mooney et al ., ; Thrivikraman et al ., ). Electrical stimulation (ES) was shown to increase DNA synthesis (Bourguignon and Bourguignon, ), activate p53 (Fukuda et al ., ), increase TGF β receptor expression (Falanga et al ., ) and upregulate fibroblast growth factor secretion (Rouabhia et al ., ). Cells also responded to exogenous ES via intracellular signalling pathways, such as phosphatidylinositol‐3‐OH kinase (PI3K)–Akt, MAPK–ERKs, integrin and Rho (Fukata et al ., ; Li et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic effects of combination treatment (MES+HS) are higher than those of MES alone or HS alone. In addition, we showed that MES+HS exerts biological effects via activation of intracellular signaling pathways such as p53 and LKB1‐AMPK axis . In clinical studies for subjects with type 2 diabetes mellitus and metabolic syndrome, MES+HS treatment significantly ameliorated the insulin resistance and inflammatory parameters without any adverse effects .…”
Section: Introductionmentioning
confidence: 86%
“…Considering that MES is a form of physiological stress, it is conceivable that the latter can activate the tumor suppressor p53, which is a key modulator of the cell cycle and apoptosis in response to cell stresses. Indeed, when cells were treated with an imperceptible voltage (1 V/cm) p53 was transiently phosphorylated at Ser‐15 by p38 MAPK (Fukuda et al, ). Therefore, it can be concluded that electrical stimulation activates p53 and may induce p53‐dependent differentiation of MSCs (Tonelli et al, ).…”
Section: Ca2+‐depended Signaling Pathway Regulates Self‐renewal and Pmentioning
confidence: 99%